Interleukin-15 Constrains Mucosal T Helper 17 Cell Generation: Influence of Mononuclear Phagocytes - Yu, Huifeng (PLoS One, 2015)
Interleukin (IL)-15 has multiple roles in innate and adaptive immunity, especially regarding CD8(+) T cells and natural killer cells. However, the role of IL-15 in regulating differentiation of T helper cell subsets and mononuclear phagocytes (MPs) in different tissues in vivo is unknown. Here we report that IL-15 indirectly regulates Th17 but not other Th subsets in the intestinal lamina propria (LP), apparently through effects on MPs. Th17 cells in the LP were more prevalent in IL-15 KO mice than their wild-type counterparts, and less prevalent in IL-15 transgenic mice than their wild-type littermates, even co-caged. MPs from the LP of these mice were sufficient to mimic the in vivo finding in vitro by skewing of cocultured wild type OVA-specific CD4(+) T cells. However, production of IL-15 or lack thereof by these MPs was not sufficient to explain the skewing, as addition or blockade of IL-15 in the cultures had no effect. Rather, a skewing of the relative proportion of CD11b(+), CD103(+) and double positive LP MP subsets in transgenic and KO could explain the differences in Th17 cells. Thus, IL-15 may influence MP subsets in the gut in a novel way that alters the frequency of LP Th17 cells.